2016 Annual Security Report (CSU Channel Islands)
Officials assigned to the University Police Department prepare this report to comply with the Jeanne Clery Disclosure of Campus Security Policy and Crime Statistics Act. This report is prepared in cooperation with the local law enforcement agencies surrounding our main campus and alternate sites, Housing & Residential Education, the Division of Student Affairs, the Dean of Students, the Title IX Coordinator, Human Resources, and Faculty Affairs. Each entity provides updated information on their educational efforts and programs necessary to ensure compliance with the Act.